Abca1 deficiency protects the heart against myocardial infarction-induced injury. (August 2016) - Louwe, Mieke C.; Lammers, Bart; Frias, Miguel A.; Foks, Amanda C.; de Leeuw, Lidewij R.; Hildebrand, Reeni B.; Kuiper, Johan; Smit, Johannes W.A.; Van Berkel, Theo J.C.; James, Richard W.; Geerling, Janine J.; Rensen, Patrick C.N.; et al.
Abstract: Background and aims: We explored the role of ATP-binding cassette transporter A1 (Abca1), in post-myocardial infarction (MI) cardiac injury. Methods: In Abca1 –/– mice, wild type (WT) mice, and WT mice transplanted with Abca1 –/– or WT bone marrow, an MI was induced in vivo . Furthermore, an ex vivo MI was induced in isolated Abca1 –/– and WT hearts. Results: Twenty-four hours and two weeks after in vivo MI induction, MI size was reduced in Abca1 –/– (−58%, p = 0.007; −59%, p = 0.03) compared to WT. Ex vivo MI induction showed no effect of Abca1 –/– on infarct size. Interestingly, two weeks after MI, Abca1 –/– mice showed higher circulating levels of B-cells (+3.0 fold, p = 0.02) and T-cells (+4.2 fold, p = 0.002) compared to WT. Bone marrow-specific Abca1 –/– tended to reduce infarct size (−43%, p = 0.12), suggesting a detrimental role for hematopoietic Abca1 after MI. Conclusions: Although Abca1 has a protective role in atherosclerosis, it exerts detrimental effects on cardiac function after MI. Highlights: We studied the role of Abca1 in post myocardial infarction cardiac injury in mice. Abca1 −/− mice and WT mice transplanted with Abca1 −/− bone marrow displayed an unanticipated reduction in infarct size. Reduced infarct size in Abca1 −/− mice was accompanied by an increase in circulating leukocytes. Our results suggest that hematopoietic Abca1 has unfavorable effects on cardiac injury following myocardial infarction.